AN ANALYSIS OF RANDOMIZED CONTROL TRIALS OF MICROBIOME ALTERATION AND DIET IN GASTRIC CANCER IN HUMANS-A SYSTEMATIC REVIEW - ANN BINU JOSEPH; SINDHU R; HARIPRIYA R; RAJMOHAN M; DINESH DHAMODHAR; LUBNA FATHIMA; PRABU D; BANU JOTHI A (The Bioscan, 2025)
Gastric cancer (GC) remains a leading cause of cancer mortality. Growing evidence links diet and the gut microbiome to GC risk and outcomes. Systematic search of PubMed, EMBASE, Cochrane CENTRAL, and Web of Science (January 2000–June 2025) following PRISMA 2020. RCTs in adults with GC or precancerous lesions evaluating H. pylori eradication, vitamins/garlic, fiber, probiotics, or synbiotics were included. Quality was appraised with the Jadad tool. Five RCTs (from 410 records) show that 2-week H. pylori eradication lowers gastric cancer incidence and mortality, with vitamin C/E/selenium and aged garlic adding mortality benefits especially in nutritionally vulnerable or non-drinkers. Perioperative fiber-enriched nutrition plus probiotics reduced diarrhoea and length of stay; multistrain probiotics improved inflammatory, immune, and nutritional markers and restored beneficial taxa. In precancerous lesions, a 12-week high-fiber diet increased SCFA-producing bacteria and reduced inflammation. Overall quality was moderate to high. Microbiome and dietary interventions—especially early H. pylori eradication, perioperative fiber/probiotics, and long-term micronutrient/garlic supplementation—offer clinically meaningful benefits across GC prevention and care. Effects appear modified by lifestyle behaviors (smoking, alcohol). Future multicentre RCTs should standardize microbiome endpoints, stratify by baseline nutrition and risk behaviors, and test individualized, microbiome-guided strategies. Clinical integration appears feasible and low risk. KEYWORDS: Gastric cancer, Helicobacter pylori eradication, gut microbiome, probiotics, diet.